تداعيات اضطرابات سلاسل التوريد العالمية على الصناعات الدوائية في مصر / The Repercussions of Global Supply Chain Disruptions on Pharmaceutical Industry in Egypt - توفيق، هيدرا ادوارد; عيسى، محمد عبد الشفيع (معهد التخطيط القومى, 2026)
استهدفت الدراسة تحليل تداعيات اضطرابات سلاسل التوريد العالمية على الصناعات الدوائية في مصر خلال الفترة (2020–2024)، مع التطبيق على أدوية مرضى السكري كنموذج للأدوية الاستراتيجية ذات الحساسية المرتفعة لتقلبات الإمداد والأسعار. واعتمدت الدراسة على المنهج الاستدلالي، مدعومًا بدراسة ميدانية استندت إلى استبيانات وُجّهت إلى عينة من شركات الأدوية سواء المنتجة أو المستوردة أو الموزعة للأدوية بالسوق المحلى. وأظهرت النتائج وجود تأثير ذي دلالة إحصائية لاضطرابات سلاسل التوريد العالمية على مستوى توافر الأدوية في السوق المصري. كما ثبت وجود علاقة معنوية بين هذه الاضطرابات وارتفاع أسعار الأدوية، حيث سجلت بعض أدوية مرضى السكري زيادات سعرية تراكمية كبيرة بلغت في بعض الحالات نحو 300% خلال فترة الدراسة. كما كشفت النتائج عن وجود فروق ذات دلالة إحصائية في درجة التأثر بين الشركات المنتجة محليًا والشركات المستوردة، بما يعكس الدور النسبي للتوطين الصناعي في الحد من آثار الصدمات الخارجية. كذلك أظهرت بيانات التجارة الخارجية استمرار العجز في الميزان التجاري الدوائي، مع ارتفاع ملحوظ في قيمة الواردات خلال عام 2024، بما يعكس استمرار الاعتماد على الخارج في توفير بعض مدخلات الإنتاج الدوائي. وانتهت الدراسة بتقديم مجموعة من التوصيات أهمها: ضرورة تعزيز مرونة سلاسل التوريد الدوائية، وتوسيع نطاق التوطين الصناعي، وتحسين آليات إدارة المخاطر اللوجستية والتمويلية، بما يسهم في دعم الأمن الدوائي وتحقيق الاستقرار السعري في السوق المصري. This The study aimed to analyze the repercussions of global supply chain disruptions on the pharmaceutical industry in Egypt during the period (2020–2024), with specific application to diabetes medications as a model for strategic drugs characterized by high sensitivity to supply and price fluctuations. The study adopted an inferential approach, supported by a field study based on questionnaires administered to a sample of pharmaceutical companies operating in the domestic market, including local manufacturers, importing companies, and distribution firms. The findings revealed a statistically significant impact of global supply chain disruptions on the availability of medicines in the Egyptian market. The results also confirmed a significant relationship between these disruptions and rising drug prices, as some diabetes medications recorded substantial cumulative price increases, reaching approximately 300% in certain cases during the study period. Furthermore, the findings indicated statistically significant differences in the degree of impact between locally manufacturing companies and importing firms, reflecting the relative role of industrial localization in mitigating external shocks. Foreign trade data also showed the persistence of a deficit in the pharmaceutical trade balance, along with a notable increase in the value of imports in 2024, underscoring the continued reliance on external sources for certain pharmaceutical production inputs. The study concluded with a set of recommendations, most notably: the need to enhance the resilience of pharmaceutical supply chains, expand the scope of industrial localization, and improve logistical and financial risk management mechanisms, thereby supporting pharmaceutical security and achieving price stability in the Egyptian market.